Effects of chicken feather keratin on smoke suppression characteristics and flame retardancy of epoxy resin. (11th June 2020) - Hu, Po; Zheng, Xinyu; Zhu, Jiwei; Wu, Baolin
Abstract : Chicken feather keratin (CK), a biomaterial that contains a large amount of nitrogen is extracted from chicken feathers and has significant potential for use as a flame retardant. In this study, CK and 9, 10‐dihydro‐9‐oxa‐10‐phosphenanthrene‐10‐oxide (DOPO) were added in different amounts to an epoxy resin (EP), and their flame retardancy and smoke suppression effects were studied. The results showed that CK exhibits a good flame‐retardancy effect and better smoke suppression characteristics than those of DOPO when added to EP. Furthermore, it greatly reduces the CO yield in smoke. While the EP samples with DOPO showed better flame‐retardancy properties than those of the samples with CK, they also produced more smoke, which had a higher CO content. Furthermore, when CK and DOPO were added to EP together, the flame‐retardancy characteristics of the samples varied with the CK/DOPO ratio. Then the pyrolysis of all samples was divided into two stages based on thermokinetics analysis and the activation energies of these samples in the two stages were investigated. Finally, the flame‐retardancy mechanism was discussed. When samples burn, the PO· free radicals derived from DOPO combine with H· and OH· to induce a quenching effect. In addition, the phosphate resulting from the decomposition of DOPO promotes the formation of the char layer. At the same time, the noncombustible gases generated during the pyrolysis of CK cause the char layer to expand and remove some of the heat. Thus, CK and DOPO synergistically improved the flame retardancy of EP.